Упростите выражение (3a/4-a-6a/a^2+16-8 a)÷a/4-a

Упростите выражение (3a/4-a-6a/a^2+16-8 a)÷a/4-a
Гость
Ответ(ы) на вопрос:
Гость
( 3а/(4-а)   -   6а/(а²+16 - 8а)  ) :    а/(4-а) =  = ( 3а/(4-а)   -  6а/[ ( 4²-2*4*a +a² )  )  :  а/(4-а)  = =  (3а/(4-а)  -    6а/(4-a)² )  :  а/(4-а) = =  ( 3а(4-a)  - 6a)/ (4-a)²       *    (4-a)/a = =  (12a -3a² -6a) / (4-a)      *   1/a = =  (6a-3a²)/(4-a)     *  1/a = =   (3a(2 - a) /  ((4-a)*a)  = =  3(2-a) / (4-a) = =  (6-3a) /(4-a)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы